NCRI phase II study of CHOP in combination with ofatumumab in induction and maintenance in newly diagnosed Richter syndrome. (5th July 2016) - Eyre, Toby A.; Clifford, Ruth; Bloor, Adrian; Boyle, Lucy; Roberts, Corran; Cabes, Maite; Collins, Graham P.; Devereux, Stephen; Follows, George; Fox, Christopher P.; Gribben, John; Hillmen, Peter; et al.
Abstract : Richter syndrome (RS) is associated with chemotherapy resistance and a poor historical median overall survival (OS) of 8–10 months. We conducted a phase II trial of standard CHOP‐21 (cyclophosphamide, doxorubicin, vincristine, prednisolone every 21 d) with ofatumumab induction (Cycle 1: 300 mg day 1, 1000 mg day 8, 1000 mg day 15; Cycles 2–6: 1000 mg day 1) (CHOP‐O) followed by 12 months ofatumumab maintenance (1000 mg given 8‐weekly for up to six cycles). Forty‐three patients were recruited of whom 37 were evaluable. Seventy‐three per cent were aged >60 years. Over half of the patients received a fludarabine and cyclophosphamide‐based regimen as prior CLL treatment. The overall response rate was 46% (complete response 27%, partial response 19%) at six cycles. The median progression‐free survival was 6·2 months (95% confidence interval [CI] 4·9–14·0 months) and median OS was 11·4 months (95% CI 6·4–25·6 months). Treatment‐naïve and TP53 ‐intact patients had improved outcomes. Fifteen episodes of neutropenic fever and 46 non‐neutropenic infections were observed. There were no treatment‐related deaths. Seven patients received platinum‐containing salvage at progression, with only one patient obtaining an adequate response to proceed to allogeneic transplantation. CHOP‐O with ofatumumab maintenance provides minimal benefit beyond CHOP plus rutuximab. Standard immunochemotherapy for RS remains wholly inadequate for unselected RS. Multinational trials incorporating novel agents are urgently needed.